How to integrate it : a practical guide to finding elementary integrals - Stewart, Seán M. (Cambridge University Press, 2018)
"While differentiating elementary functions is merely a skill, finding their integrals is an art. This practical introduction to the art of integration gives readers the tools and confidence to tackle common and uncommon integrals. After a review of the basic properties of the Riemann integral, each chapter is devoted to a particular technique of elementary integration. Thorough explanations and plentiful worked examples prepare the reader for the extensive exercises at the end of each chapter. These exercises increase in difficulty from warm-up problems, through drill examples, to challenging extensions that illustrate such advanced topics as the irrationality of pi and e, the solution of the Basel problem, Leibniz's series and Wallis's product. The author's accessible and engaging manner will appeal to a wide audience, including students, teachers and self-learners. It can serve as a complete introduction to finding elementary integrals, or as a supplementary text for any beginning course in calculus."--